2022
DOI: 10.1177/15412040221089235
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Prevalence and Predictive Validity of Protective Factors in a Sample of Justice-Involved Youth

Abstract: Research on strengths and violent behavior in justice-involved youth suggests that the prevalence and predictive validity of strength factors vary as a function of gender. Interviews conducted between 2009 and 2012 with 185 justice-involved Canadian youth ( N female = 84, N male = 101; 67% violent index offence) were coded retrospectively using two strength measures for violence prediction: the protective domain of the Structured Assessment of Violence Risk in Youth (SAVRY), and the Structured Assessment of Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 56 publications
(108 reference statements)
2
11
1
Order By: Relevance
“…Our findings were consistent with the moderate relationships reported by de Ruigh et al ( 2021), Kleeven et al (2022) and Lovatt et al (2022). They contrasted somewhat with Chu et al (2020)'s large AUC and with Goodwin et al (2022) and Koh et al (2022), who found that the SAPROF-YV was a more modest predictor of any recidivism. The SAPROF-YV was a weak predictor of violent recidivism, which is consistent with Goodwin et al (2022) 2022), who found the tool to be a moderate predictor of violent recidivism.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings were consistent with the moderate relationships reported by de Ruigh et al ( 2021), Kleeven et al (2022) and Lovatt et al (2022). They contrasted somewhat with Chu et al (2020)'s large AUC and with Goodwin et al (2022) and Koh et al (2022), who found that the SAPROF-YV was a more modest predictor of any recidivism. The SAPROF-YV was a weak predictor of violent recidivism, which is consistent with Goodwin et al (2022) 2022), who found the tool to be a moderate predictor of violent recidivism.…”
Section: Discussionsupporting
confidence: 92%
“…We did not make any predictions about the factor structure of the SAPROF-YV given the lack of prior research. Evidencing a direct-or promotiveeffect, we hypothesized that the SAPROF-YV total score would discriminate between recidivists and nonrecidivists and significantly predict recidivism, consistent with prior research (Chu et al, 2020;de Ruigh et al, 2021;Kleeven et al, 2022;Koh et al, 2022) and that it would predict recidivism better for males than for females (Goodwin et al, 2022;Lovatt et al, 2022). Given the lack of clear theoretical or empirical (Chu et al, 2020;de Ruigh et al, 2021;Kleeven et al, 2022;Koh et al, 2022;Lovatt et al, 2022) justification, we did not hypothesize that the SAPROF-YV would provide incremental validity to a measure of risk (the YLS/CMI) in predicting recidivism.…”
Section: The Present Studymentioning
confidence: 68%
See 1 more Smart Citation
“…These SAVRY indices have been shown to predict multiple types of recidivism outcomes with various populations of justice-involved adolescent males, although the evidence is more equivocal both with justice-involved adolescent females and for the summed total of the Protective Factor items (cf. Goodwin et al, 2022; Muir et al, 2020; Olver et al, 2009; Soderstrom et al, 2020; Viljoen et al, 2008; Vincent et al, 2011). But, to date, the potential risk, promotive, and mixed effects of any SAVRY items have not been investigated.…”
Section: Farrington Et Al’s (2016) Risk Promotive and Mixed Factorsmentioning
confidence: 99%
“…The literature on the predictive validity by gender is mixed. Some studies have found the SAVRY to be an excellent predictor of recidivism among males (Goodwin et al, 2022; Schmidt et al, 2011), while others have found it works well for both gender groups (Gammelgård et al, 2008; Meyers & Schmidt, 2008; Muir et al, 2020; Penney et al, 2010; Shepherd et al, 2014a). These studies underscore the importance of assessing the psychometric properties and predictive validity of the SAVRY by gender and race.…”
Section: Introductionmentioning
confidence: 99%